Diversidad de vocabulario en los preescolares. Aportes para valorar su competencia léxica. - Murillo Rojas, Marielos (2012)
This article is analyzing the lexical diversity of 101 children from four to six years old and eleven months that attended during the year 2008 to six institutions of preschool education in the Metropolitan Area, Costa Rica. The lexical richness is valued from the diversity of words of lexical content (nouns, adjectives and verbs) in oral narratives of 50 statements, calculated with the Pd50 formula.